Cell death following the loss of ADAR1 mediated A-to-I RNA editing is not effected by the intrinsic apoptosis pathway - Walkley, Carl R. (Cell Death Dis, 2019)
Modifications of RNA, collectively termed as the epitranscriptome, are widespread, evolutionarily conserved and contribute to gene regulation and protein diversity in healthy and disease states. There are >160 RNA modifications described, greatly exceeding the number of modifications to DNA. Of these, adenosine-to-inosine (A-to-I) RNA editing is one of the most common. There are tens of thousands of A-to-I editing sites in mouse, and millions in humans. Upon translation or sequencing an inosine base is decoded as guanosine, leading to A-to-G mismatches between the RNA and DNA. Inosine has different base pairing properties to adenosine and as a result editing not only alters the RNA code but can also change the RNA structure. In mammals A-to-I editing is performed by ADAR1 and ADAR2. A feature of murine loss of function ADAR1 alleles is cell death and a failure to survive embryogenesis. Adar1(−/−) and editing deficient (Adar1(E861A/E861A)) mice die between E11.75–13.5 of failed hematopoiesis. Strikingly this phenotype is rescued by the deletion of the cytosolic dsRNA sensor MDA5 or its downstream adaptor MAVS, a mechanism conserved in human and mouse. Current literature indicates that the loss of ADAR1 leads to cell death via apoptosis, yet this has not been genetically established. We report that blockade of the intrinsic (mitochondrial) apoptosis pathway, through the loss of both BAK and BAX, does not rescue or modify the cellular phenotype of the fetal liver or extend the lifespan of ADAR1 editing deficient embryos. We had anticipated that the loss of BAK and BAX would rescue, or at least significantly extend, the gestational viability of Adar1(E861A/E861A) embryos. However, the triple mutant Adar1(E861A/E861A) Bak(−/−) Bax(−/−) embryos that were recovered at E13.5 were indistinguishable from the Adar1(E861A/E861A) embryos with BAK and BAX. The results indicate that cell death processes not requiring the intrinsic apoptosis pathway are triggered by MDA5 following the loss of ADAR1.